Taxonomic Revision of Staurogyne (Nelsonioideae, Acanthaceae) in the Neotropics - Braz, Denise Monte; Monteiro, Reinaldo [UNESP] (Magnolia Press, 2017)
Twenty-eight species of Staurogyne are recognized from the Neotropics, where the genus is distributed from Mexico to southern Brazil. The study of herbarium specimens, especially from Brazil and other South American countries, including historical collections from many European herbaria, resulted in the recognition of numerous new geographical records. Morphological characters of diagnostic importance are discussed for the genus and species, for which aspects of the inflorescence, corolla, gynoecium and indument are important for identification. In Neotropical Staurogyne, the corolla may have two basic forms: 1) short, infundibular, and white (often with markings on the limb and throat), and 2) long, tubular, and yellow or red. Species with the latter form of the corolla are restricted to southeastern Brazil. Eight synonymizations and one lectotyfication are proposed, while a key to species, descriptions, illustrations and comments on taxonomy, phenology and geographical distribution are provided.
Keywords: Brazilian flora; description; morphology; synonymization; lectotypification